Welding of Gapura from Iron - Bintang, Muhammad; Eka Pranomo, Gatot (Universitas Ibn Khaldun, 2022)
The manufacture of a welcome iron arch using a type of light iron iron with a thickness of each is for a 1.2 cm support pole and for its top 0.8 cm. The creation of the gate aims as the identity of the place name. In the selection of gapura raw materials using swot data method, the results of the analysis obtained raw materials meet the criteria of use and affordable. The use of paint is agreed to avoid corrosion in light iron due to water. Hopefully the welcome iron gap can last a long time and benefit the surrounding community.